Structural and qualitative evaluation of microscopy and directly observed treatment centers under revised national tuberculosis control programme in Nanded city of Maharashtra - Vijay Manohar Bhagat; Prakash Laxminarayan Gattani (Wolters Kluwer Medknow Publications, 2011)
Structural and qualitative evaluation of Revised National Tuberculosis Control Programme (RNTCP) is important to determine actual status of the programme in the field settings and to uncover the concealed gaps. The present cross-sectional study assessed the infrastructural facilities and quality of services provided through microscopy and directly observed treatment (DOT) centers at Nanded city of Maharashtra. The investigator made on spot observation on the activities at microscopy and DOT centers and assessed the infrastructural facilities using an observational checklist. Expert microbiologist cross checked the microscopy report done by the laboratory technicians. It revealed that retrieval mechanism was not functioning in more than half of the DOT centers. Only 5 DOT providers were trained in RNTCP. Stock of sputum containers, methylene blue, and carbol fuchsin was found to be inadequate at some microscopy centers. Half of the laboratory technicians reported high false positive result in spite of being trained. Improvement of infrastructural and logistic support along with the refreshing training for the workers are needed for effective implementation of RNTCP.